2018
DOI: 10.1111/codi.14114
|View full text |Cite
|
Sign up to set email alerts
|

Decreased risk for microscopic colitis and inflammatory bowel disease among patients with reflux disease

Abstract: Gastro-oesophageal reflux disease is inversely associated with all forms of inflammatory bowel disease, such as MC, UC, or CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…On the other hand, acid-related diseases are not associated with other enteric diseases that can promote renal stone formation. A study by Sonnenberg et al (36) demonstrated that gastro-esophageal reflux disease (GERD) is inversely associated with all forms of inflammatory bowel diseases that are associated with an increased risk of stone formation due to increased urinary oxalate caused by fat malabsorption. On the contrary, subjects with gastroesophageal reflux-type symptoms showed an higher risk of irritable bowel syndrome that has not been associated with renal stone disease (37).…”
Section: Limitationsmentioning
confidence: 99%
“…On the other hand, acid-related diseases are not associated with other enteric diseases that can promote renal stone formation. A study by Sonnenberg et al (36) demonstrated that gastro-esophageal reflux disease (GERD) is inversely associated with all forms of inflammatory bowel diseases that are associated with an increased risk of stone formation due to increased urinary oxalate caused by fat malabsorption. On the contrary, subjects with gastroesophageal reflux-type symptoms showed an higher risk of irritable bowel syndrome that has not been associated with renal stone disease (37).…”
Section: Limitationsmentioning
confidence: 99%